Parental Alienation - Father as a Rejected Parent - Üner Altuntaş, Gülden Elçim; Ziyalar, Neylan (The Bulletin of Legal Medicine, 2018)
Objective: Parental Alienation is defined as an unfair, continuous and persistent rejection of a parent in the influence of the other parent. In this study, it was aimed to bring out the mechanisms and the origins affecting the Parental Alienation and to expose the perceptions of the father as rejected parent. Materials and Methods: The study sample consists of 111 participants -38 fathers and 73 children- from 54 divorcing families at Istanbul Courthouse 9th Family Court. Social Demographic Data Form for determining the demographic features of participants, Baker Alienation Questionnaire for determining Parental Alienation in and Parental Attitude Research Instrument (PARI) for determining parental attitudes of fathers were used. In order to clarify the fathers’ perspective on Parental Alienation in-depth interview was conducted. Quantitative data were calculated by descriptive statistics, Chi Square Test and Kruskal Wallis Test, significance level was accepted as .05. Qualitative data, collected from in-depth interviews, were analyzed by the “content analysis”. Results: The study exhibited that 42.5% of participant children had Parental Alienation to their fathers. The claims of domestic violence and physical violence against children, the father-child contact after separation and fathers’ ages were associated with the Parental Alienation. Children tended to show Parental Alienation behaviors to the fathers more frequently if there was alienation in siblings and the children of the fathers who had authoritarian, democratic and protective attitudes in childrearing were shown less Parental Alienation. According to the content analysis 4 major categories as; accusations against mothers, feelings of weakening in paternal identity and loss in father’s rights and memories about their fatherhood experiences before the separation were determined. Conclusion: Parental Alienation is frequently seen in the divorce incidents and the rejected fathers express more troubles.